Enhancing Students’ Narrative Writing Ability Using Picture-Cued Technique Combined with Story Mapping - Yudhi Pramawati, Anak Agung Istri (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2025)
Writing skill is one of the four essential language skills that must be mastered by students. However, many students continue to struggle with writing. The objective of this classroom action research was to investigate whether the writing skill of the seventh-grade students of PoMe Educircle in the academic year 2024/2025 could be improved through the implementation of the Picture-Cued Technique combined with Guided Writing. To achieve this goal, the researcher conducted a pre-test, post-tests, and administered a questionnaire. The result of the pre-test showed that the students' initial writing ability was relatively low, with an average score of 55.62. After applying the combined technique, post-tests were administered at the end of each cycle, showing improvement to 61.47 in cycle I and 79.53 in cycle II. The significant improvement indicated that the technique was effective. Furthermore, a questionnaire was distributed at the end of cycle II to obtain additional supporting data. It revealed that students demonstrated increased motivation and a more positive attitude toward writing after the implementation. In conclusion, this study showed that the writing skill of the seventh-grade students of PoMe Educircle could be effectively improved through the Picture-Cued Technique combined with Guided Writing. The students also responded positively to the learning process.